A comparative study of different immunoassays to detect specific antibodies to Echinococcus spp. in human sera - Fecková M.; Antolová D.; Reiterová K. (Helminthologia, 2020)
Human echinococcosis, one of the most serious of parasitic zoonoses, is caused by the larval stages of taeniid cestodes of the genus Echinococcus. The study aimed to assess the reliability of the detection of specific antibodies to E. multilocularis and E. granulosus s.l. in human sera and to compare their diagnostic potential for their utilization in the practice. In the study, the somatic antigen of E. multilocularis (AgEm), antigen B (AgB), and the hydatid fluid antigen of E. granulosus and two commercial ELISA kits – Echinococcus granulosus (Bordier Affinity Products, Crissier, Switzerland) and NovaLisaTM Echinococcus IgG (NovaTec Immunodiagnostica, Germany) – were compared. Sera of patients with alveolar and cystic echinococcosis, and with different parasitic/other infections were used to evaluate the sensitivity, specificity and cross-reactivity of in-house and commercial ELISA methods. AgEm presented the highest values regarding the diagnostic indicators, showing 100 % specificity and 90.0 % sensitivity. The tests for serological diagnostics of cystic echinococcosis were less sensitive and specific. The Echinococcus granulosus kit had 83.8 % specificity and 88.2 % sensitivity, while AgB and AgHF showed 85.0 % and 86.3 % specificity, and 76.5 % and 100 % sensitivity, respectively. NovaLisaTM Echinococcus IgG proved to have 95.7 % specificity and 77.8 % sensitivity. The results point out that the combination of different serological tests and approaches in accordance with clinical and imaging findings is still essential to prove the correct diagnosis in suspected patients.